Strengthening the relationship between digitalization and the national smart economy model for implementation of the strategy of innovative development - ZRYBNIEVA, IRYNA; Bodrov, V.; Sazonova, S.; Sydoruk, I.; Orlenko, O. (Financial and credit activity-problems of theory and practice, 2023)
Modern economy development is inseparably concerned with the use of the most mod-ern and advanced information technologies. Therefore, scientists’ attention in terms of the issues of digitalisation and innovative development is constantly growing. In this paper studies different scientific views on the specifics of digitalisation of economic sys-tems and building a modern smart economy of the future were used. The purpose of the study is to prove the relationship between the processes of digitalization and the formation of an innovative model of the smart economy in Ukraine. To achieve this goal, in the article statistical data on the state of innovative development of the Ukrainian economy and Ukrainian enterprises were analysed; the directions of the strategy of innovative development at the national level implementation was specified. The study substantiates that currently the national economy is on the way to a smart society for-mation, and most innovative initiatives are carried out at the expense of business, while the state uses regulatory levers without active financial participation. The mutual influ-ence of digitalisation processes and implementation of the innovation development strategy is determined. It was established that digitalisation processes are essential and extremely important for the formation of a national model of the smart economy, as they are complex and applied, but not concentrated in a particular area or industry. At present, the national model of the smart economy cannot be formed without state sup-port that is provided through the development and implementation of the innovation development strategy. The state has the capabilities and sufficient levers to stimulate the introduction of modern digital technologies and the development of an innovative component of scientific research that can be implemented in the practical activities of Ukrainian enterprises and organizations in the future.
Keywords: digitalization, digitaleconomy, development strategy, innovative development, scientific progress, development, economic recovery